A CASE STUDY ON FISH AFFORDABILITY AS MAIN PROTEIN DIET OF LOW-INCOME PEOPLE IN DHAKA SOUTH, BANGLADESH (Bioresearch Communications, 2022)
The low-income population in the study area consumes fish in a selective manner. They prefer frequently purchase fish at lower price. Study revealed that 16 fish species under 6 orders were highly consumed by the targeted group. Order Cypriniformes was the most dominant (46%) group according to their fish consumption pattern. Rui, Labeo rohita was the highly prioritized fish, rather than this, telapia, pungus, koi and prawn were also in their priority list due to availability and low prices in the market. Among all types of fishes, 85% were culture and 15% were capture fishes respectively. Fish consumption rate in low-income people varies significantly on the basis of their income and age group. Fish day of low-income people ranging from 4-17 days per month. Most of the respondents (89%) were aware of nutritional value of fish but considering the prices of fishes and low wages most of the time they were not able to meet their daily requirement of fish protein. Thus, this finding will provide the real scenario of fish protein intake of that targeted economic group and help policy makers, NGOs, national and international donors for better understand to cope up malnutrition for future generation.Bioresearch Commu. 9(1): 1215-1224, 2023 (January)